2018
DOI: 10.1111/petr.13235
|View full text |Cite
|
Sign up to set email alerts
|

Cell phone support to improve medication adherence among solid organ transplant recipients

Abstract: For many adolescent and young adult solid organ transplant recipients, medication non-adherence is a mortal issue. This study investigated the feasibility, acceptability, and potential efficacy of a 12-week cell phone support intervention to improve immunosuppressant medication adherence. A small sample (N = 8) of non-adherent adolescent and young adult transplant recipients, aged 15-20.5 years, was enrolled. Cell phone support consisted of short calls each weekday including medication reminders, discussion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
12
0
3
Order By: Relevance
“…The study included a once a week call by a trained adherence facilitator to address adherence barriers and facilitate problem‐solving and identify resources. Of 17 patients identified as eligible, only nine (52.9%) consented to participate despite a financial incentive and limited time burden, and only eight completed the intervention 36 . The Sayegh study illustrates the real day‐to‐day challenges of maintaining engagement of our non‐adherent adolescents in behavior change.…”
Section: Healthcare System–level Factors That Contribute To Non‐adhermentioning
confidence: 99%
“…The study included a once a week call by a trained adherence facilitator to address adherence barriers and facilitate problem‐solving and identify resources. Of 17 patients identified as eligible, only nine (52.9%) consented to participate despite a financial incentive and limited time burden, and only eight completed the intervention 36 . The Sayegh study illustrates the real day‐to‐day challenges of maintaining engagement of our non‐adherent adolescents in behavior change.…”
Section: Healthcare System–level Factors That Contribute To Non‐adhermentioning
confidence: 99%
“…71,72 Randomized trials that investigate multicomponent interventions incorporating socioeconomic-, treatment-, condition-, and patient-related factors are needed. 71 Pilot studies investigating the implementation of a peer mentoring program, 73 group meetings, 74 and daily phone reminders 75 in adolescent transplant recipients have shown promise and warrant further evaluation.…”
Section: Adherence Improvement In Pediatric Transplantationmentioning
confidence: 99%
“…These are patients already demonstrating challenges with the treatment regimen, so attrition at this rate and attrition among the most non‐adherent patients was expected. A meta‐analysis of mHealth approaches with patients experiencing chronic illness reported an aggregated attrition rate of 43% across studies 45,74 . Other mHealth intervention pilot studies targeting non‐adherence in pediatric transplantation have reported similar high levels of attrition 75 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of mHealth approaches with patients experiencing chronic illness reported an aggregatedattritionrateof43%acrossstudies. 45,74 OthermHealth interventionpilotstudiestargetingnon-adherenceinpediatrictransplantation have reported similar high levels of attrition. 75 Patients withnon-adherencearelesslikelytoberecruitedintoresearch, 72,76 and recruiting only adherent patients with more consistent clinical attendanceleavesmanystudiesunabletoexaminetheimpactofthe interventions aiming to promote medication adherence.…”
Section: Limitationsmentioning
confidence: 96%